2016
DOI: 10.1111/1556-4029.13325
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of Sperm and the Development of Time Since Intercourse (TSI) Guidelines in Sexual Assault Cases at Forensic Science Ireland, Dublin, Ireland

Abstract: The persistence of sperm using confirmatory microscopic analysis, the persistence of sperm with tails, time since intercourse (TSI) analysis, and results from the acid phosphatase (AP) reaction from approximately 5581 swabs taken from circa 1450 sexual assault cases are presented. The observed proportions of sperm in the vagina and anus declines significantly after 48 h TSI, and sperm on oral swabs were observed up to 15 h TSI. The AP reaction as a predictor of sperm on intimate swabs is questioned. All AP rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…-Morrison [172] detected spermatozoa 12 and 9 d after intercourse in the cervical and vaginal samples respectively, but noted that detection rate decreased progressively after 48 h. -A study by Casey et al [173] of the results of 1450 cases observed the longest sperm persistence in the vagina to be 96 h after intercourse with significant decline in detection after 18 h and again after 48 h. The same study noted that, on rare occasions, spermatozoa were detected in the anal and oral samples 48 h after the alleged offence, however rapid decline in detection was reported after 6 and 15 h respectively. -Hellerud et al [174] h, 65 h, 46 h and 6 h after the alleged offence, respectively.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…-Morrison [172] detected spermatozoa 12 and 9 d after intercourse in the cervical and vaginal samples respectively, but noted that detection rate decreased progressively after 48 h. -A study by Casey et al [173] of the results of 1450 cases observed the longest sperm persistence in the vagina to be 96 h after intercourse with significant decline in detection after 18 h and again after 48 h. The same study noted that, on rare occasions, spermatozoa were detected in the anal and oral samples 48 h after the alleged offence, however rapid decline in detection was reported after 6 and 15 h respectively. -Hellerud et al [174] h, 65 h, 46 h and 6 h after the alleged offence, respectively.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Research on reproduction and contraception has provided numerous useful insights into the characteristics of sperm following deposition into the female gynecologic tract. In the living, some of these events may impact the DNA quality of sperm collected and subsequently tested in a forensic setting . DNA degradation or sperm DNA fragmentation consists of single and double strand DNA breaks due to oxidative stress and apoptotic activity that occurs during the sperm cell's lifetime .…”
Section: Discussionmentioning
confidence: 99%
“…The perpetrator may kiss many parts of the victim's body, may hit the victim, rip their hair as they grasp them, or violently rip off their clothes. The victim may be forcefully penetrated in his/her mouth, anus, or vagina [9], and then, the sexual act may occur involving anal or vaginal penetration-with or without ejaculation [18].…”
Section: Introductionmentioning
confidence: 99%